Fu you zhi dao Mayfly island - Ye, Evergreen; Li, Shang-Chiao (Xin shi jie, 2020)
"In the near future, when exosystems on Earth are collapsing, the only paradise, MayflyIsland, is considered to be a bad omen. In this age of apocalypse, how will people see the continuation of life?" -